Problem pojmovanja in klasificiranja motenj osebnosti - Benedik, Emil (Psihološka obzorja (Ljubljana), 1997)
Personality disorders (DSM-IV, ICD-10) describe some specific clinical pictures from the broad fields of disorders of personality, but it is not clear what they really mean and what is their relationship with other mental disorders. Theories of personality and researches from this area could give usbetter answers to such questions.
Keywords: osebnostna psihologija; motnje; klasifikacija